A reconfiguração do regime de colaboração federativa no Brasil: atuação e influência do Movimento Colabora Educação - Sena, Hélio Cleidilson de Oliveira (Universidade do Vale do Rio dos Sinos, 2025)
This thesis had the following research problem: how does the Movement Collaborates Education (MCE) re-enacts the understanding about the regime of collaboration between federal entities? As a general objective, the research sought to understand how the regime of collaboration between federal entities in Brazil is constituted. As specific objectives, the research sought to explain the influence of MCE in the production of a collaborative regime between federal entities in the context of new forms of network governance; identify and analyze concepts and practices (forms of action) that characterize the collaboration regime of the MCE; and reflect on the implications of this collaboration regime for school education. The methodology used included documentary analysis, and the empirical material was composed of legislation in the educational area and 16 e-books from MCE and partners. The work presents a mapping of the activities and publications of the MCE, carried out through its website; a brief history of the Inter-American Development Bank; the literature review, verifying the works that approach this research; a discussion on the transformations of contemporary society and the challenges to education, with theoretical-epistemological propositions; besides the analysis of empirical material. This analysis was carried out from four analytical categories: the regime of collaboration through legislation; the e-books, the actors and the partners of the MCE; the understanding of the regime of collaboration by the MCE and the practices that characterize it; and the improvement of educational indicators and the implications of the collaborative regime re-enrolled by the MEC for education. Among the main findings of the research, stand out: the survey and mapping of MCE data, which contributed to future studies in the educational area, showing how business actors are acting in education; the literature review, by means of which the scarcity of studies related to the cut proposed in this thesis and showed the originality and relevance of the research; the historical panorama of the IDB, which pointed out how the supranational actors have interfered in the educational guidelines; the discussion of the transformations of contemporary society, from globalization and neoliberal rationality, which highlights the effects of competitiveness, performativity and merit in the conduct of governments and governed; and the analyses, which pointed out how the business actors, in the case studied, the MCE, have guided and influenced the educational practices, re-inscribing the regime of collaboration.
Keywords: Regime de colaboração; Movimento Colaboração Educação; Racionalidade neoliberal; Parcerias educacionais; Governança em rede; Collaboration regime; Movement Collaboration Education; Neoliberal rationality; Educational partnerships; Network governance; ACCNPQ::Ciências Humanas::Educação